Improving English Listening Skill Trough by Spotify Songs - Faisal Faisal; Anggraini Anggraini (Asosiasi Dosen Muda Indonesia, 2025)
In terms of global distribution, English is the most frequently spoken language. Therefore, in order to communicate at an international level, the student's communication abilities are required. There are numerous approaches to improve language skills, each with its own distinct set of characteristics. The development of music streaming apps such as Spotify ushered in a new way of listening to music. Daniel Ek and Martin Lorentzon founded Spotify in 2008. Spotify was called after a sentence that Ek and Lorentzon randomly blurted. Ek misheard the phrase